To the issue of medical secrets In the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article analyzes the concept of confidentiality as part of privacy. It examines the issues of legal regulations to ensurepatient confidentiality in the Republic of Kazakhstan, as well as reveals the problems of practical implementation.Key words: health, personal life, patient confidentiality, access to information, privacy.